Technical and economic optimization of subcritical, wet expansion and transcritical Organic Rankine Cycle (ORC) systems coupled with a biogas power plant. (1st February 2018) - Dumont, Olivier; Dickes, Rémi; De Rosa, Mattia; Douglas, Roy; Lemort, Vincent
Highlights: Coupling an organic Rankine cycle system to a biogas power plant. Thermo-economic optimization of the ORC unit (architecture, fluid, components). Economic analysis of two study cases is presented with optimal ORC configurations. Abstract: Generally, >40% of the useful energy (cooling engine and exhaust gases) are wasted by a biogas power plant through the cooling radiator and the exhaust gases. An efficient way to convert this waste heat into work and eventually electricity is the use of an organic Rankine cycle (ORC) power system. Over the last few years, different architectures have been widely investigated (subcritical, wet expansion and trans-critical). Despite the promising performances, realistic economic and technical constraints, also related to the application, are required for a meaningful comparison between ORC technologies and architectures. Starting from the limited literature available, the aim of the present paper is to provide a methodology to compare sub-critical, trans-critical and wet expansion cycles and different types of expanders (both volumetric and turbomachinery) from both technical and economic point of view, which represent one of the main novel aspects of the present work. In particular, the paper focuses on the thermo-economic optimization of an ORC waste heat recovery unit for a 500 kWe biogas power plant located in a detailed regional market, which was not investigated yet. By means of a genetic algorithm, the adopted methodology optimizes a given economic criteria (Pay-Back Period, Net Present Value, Profitability Index and Internal Rate of Return) while respecting technical constraints (expander limitations) and thermodynamic constraints (positive pinch points in heat exchangers, etc.). The results show that optimal ORC solutions with a potential of energy savings up to 600 MWh a year and with a pay-back period lower than 3 years are achievable in the regional market analysed.